2018
DOI: 10.1007/s00253-018-9037-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Achilles heels of the laurel wilt pathogen and its beetle vector

Abstract: Ambrosia beetles harbor fungal symbionts that serve as food sources for larvae and adults. These beetles lay their eggs along tunnels in xylem sapwood, which is the substrate for fungal growth. Symbiotic fungi of the genus Raffaelea found in invasive and indigenous ambrosia beetles include the highly virulent plant pathogen Raffaelea lauricola affecting members of the Lauraceae family. R. lauricola is responsible for the deaths of > 500 million trees since 2005. Infection by as few as 100 spores can kill a hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Insects, like many other organisms, live in association with bacterial and fungal symbionts (Douglas, 2015; Gurung, Wertheim & Falcao Salles, 2019), which can have a positive (i.e., mutualistic), negative (i.e., parasitic) or neutral (i.e., commensalistic) impact on their host’s fitness. These symbionts can also facilitate (Lu et al, 2010; Himler et al, 2011; Adams et al, 2011; Vilcinskas et al, 2013) or limit (Zhou et al, 2018; Umeda & Paine, 2019) the invasion process of their insect host. When invading a new environment, insects and their microorganisms experience biotic and abiotic forces that can lead to the loss of part of the microbiome (Lester et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insects, like many other organisms, live in association with bacterial and fungal symbionts (Douglas, 2015; Gurung, Wertheim & Falcao Salles, 2019), which can have a positive (i.e., mutualistic), negative (i.e., parasitic) or neutral (i.e., commensalistic) impact on their host’s fitness. These symbionts can also facilitate (Lu et al, 2010; Himler et al, 2011; Adams et al, 2011; Vilcinskas et al, 2013) or limit (Zhou et al, 2018; Umeda & Paine, 2019) the invasion process of their insect host. When invading a new environment, insects and their microorganisms experience biotic and abiotic forces that can lead to the loss of part of the microbiome (Lester et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the spread of several species has been limited by climatic conditions (e.g., humidity, temperature). Exotic ambrosia beetles are indeed able to survive only in areas suitable for the growth of their fungal symbionts (Marini et al, 2011; Rassati et al, 2016a; Rassati et al, 2016b; Zhou et al, 2018; Umeda & Paine, 2019). This scenario could however change if an exotic beetle is able to acquire native fungi from the invaded environment.…”
Section: Introductionmentioning
confidence: 99%
“…We used a recursive partitioning algorithm to predict host and environmental factors that were involved in laurel wilt disease incidence levels, and found that increased maximum temperatures, high relative humidities, and high wind speeds along with small stem diameters limited disease incidence within a plot. A recent paper found that found that temperatures above 26°C inhibited colony growth in R. lauricola (Zhou et al 2018). Another recent study found that the vector X. glabratus is sensitive to high temperatures and increased relative humidity, with limited flight activity (Brar et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the spread of several species has been limited by climatic conditions (e.g., humidity, temperature). Exotic ambrosia beetles are indeed able to survive only in areas suitable for the growth of their fungal symbionts (Marini et al, 2011;Rassati et al, 2016b,a;Zhou et al, 2018;Umeda & Paine, 2019). This scenario could however change if an exotic beetle is able to acquire native fungi from the invaded environment.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%
“…Insects, like many other organisms, live in association with bacterial and fungal symbionts (Douglas, 2015;Gurung, Wertheim & Falcao Salles, 2019), which can have a positive (i.e., mutualistic), negative (i.e., parasitic) or neutral (i.e., commensalistic) impact on their host's fitness. These symbionts can also facilitate (Lu et al, 2010;Himler et al, 2011;Adams et al, 2011;Vilcinskas et al, 2013) or limit (Zhou et al, 2018;Umeda & Paine, 2019) the invasion process of their insect host. When invading a new environment, insects and their microorganisms experience biotic and abiotic forces that can lead to the loss of part of the microbiome (Lester et al, 2017).…”
Section: Introductionmentioning
confidence: 99%